Mode of inheritance for biochemical traits in genetically engineered cotton under water stress. (18th August 2015) - Abid, Muhammad Ali; Malik, Waqas; Yasmeen, Azra; Qayyum, Abdul; Zhang, Rui; Liang, Chengzhen; Guo, Sandui; Ashraf, Javaria
Abstract : The optimal level of Bt toxin in Bt cotton is imperative for sustainability and adoption of Bt cotton under water stressed and non-stressed environments. We investigated the mode of inheritance and association of various drought tolerance biochemicals traits with Bt toxin under normal and water stressed conditions. We observed non-additive gene action coupled with low heritability estimates for all studied biochemical traits. The different kinds of association between Bt toxin and biochemical traits proved to be a simple innovative strategy. Furthermore, it is concluded that different biochemical traits can serve as a potential biochemical markers in future for breeding drought tolerant Bt cotton. Abstract: Drought is an abiotic environmental stress that can significantly reduce crop productivity. We examined the mode of inheritance for different biochemical traits including total soluble proteins, chlorophyll a, chlorophyll b, total chlorophyll, carotenoids, total phenolic contents and enzymatic antioxidants (superoxide dismutase, peroxidase and catalase), and their relationship with Bacillus thuringiensis ( Bt ) toxin under control and drought conditions. Eight genetically diverse cotton genotypes were selfed for two generations to ensure homozygosity. Fifteen F 1 hybrids were developed by crossing five non- Bt female lines with three Bt male testers. The F 1 hybrids and eight parents were finally evaluated under control (100 % field capacity (FC)) and drought (50 % FC) conditions in 2013. The biochemical traits appeared to be controlled by non-additive gene action with low narrow sense heritability estimates. The estimates of general combining ability and specific combining ability for all biochemical traits were significant under control and drought conditions. The genotype-by-trait biplot analysis showed the better performance of Bt cotton hybrids when compared with their parental genotypes for various biochemical traits under control and drought conditions. The biplot and path coefficient analyses revealed the prevalence of different relationships between Cry1Ac toxin and biochemical traits in the control and drought conditions. In conclusion, biochemical traits could serve as potential biochemical markers for breeding Bt cotton genotypes without compromising the optimal level of Bt toxin.